Thermodynamic stability and drug-binding properties of oligodeoxyribonucleotide duplexes containing 3-deazaadenine:thymine base pairs. - Lever, C; Li, X; Cosstick, R; Ebel, S; Brown, T (1993)
We have used ultraviolet melting techniques to study the effect on stability of incorporating the nucleoside analogue 2'-deoxy-3-deazaadenosine (d3cA) into the duplex 5'-d(CGCAATCG)-3'-d(GCGTTAGC). Our results demonstrate that the successive replacement of dA by d3CA increasingly destabilises the duplex. The destabilising effect of this analogue is considerably enhanced as the pH is lowered and the results are consistent with protonation of 3-deazaadenine (probably at N-1) contributing to duplex destablisation. Surprisingly, the incorporation of d3CA does not significantly affect the binding of distamycin-A.